Business Ethics for Micro Finance Institutions - Balaji, R. (Prabandhan: Indian Journal of Management, 2010)
Business ethics are a form of applied ethics that examines ethical principles and moral or ethical problems that arise in a business environment. Ethics are a set of values and principles that we strongly believe and follow. It is learning what is right or wrong, and then doing the right thing. The concept of business ethics has come to mean various things to various people, but generally, it's coming to know what is right or wrong at the workplace and doing what's right.